Platformization in the built environment: the political techno-economy of Building Information Modeling. - Boeva, Yana; Braun, Kathrin; Kropp, Cordula (Science as Culture, 2024)
The digital transformation of architecture, engineering, and construction (AEC) is being hailed as a panacea for the sectors' problems, with major actors in government and business promoting it as a benevolent harbinger of greater efficiency, productivity, better quality, and environmental performance. However, advancing digitalization in AEC is intertwined with a distinct political-economic logic that involves new constraints, dependencies, and a reconfiguration of power relations. Specifically, Building Information Modeling (BIM) as a digital convergence of three-dimensional building models, databases, and interfaces for multidisciplinary collaboration operates as a runway technology for digitalization and an entry point for platformization impelled by global software giants, such as this article's empirical case of software company Autodesk and its BIM product portfolio shows. BIM's linkage of governmental policy strategies with the techno-economic platform logic of software subscription models, open application programming interfaces, and cloud-enabled collaboration ensures management and control of construction data and software interoperability. At the same time, BIM's techno-economic and political configuration facilitates a near-monopolistic structure in the global architecture and construction software market. It thus grants one hegemonic company immense power to define what formats, standards, and data for building models and design processes are being used in creating the built environment. The expansive, intersecting logics of assetization, platformization, and datafication have been taking hold in the AEC sector, raising questions about their stratifying effects in the built environment and society.